2006
DOI: 10.2225/vol9-issue3-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative analysis of genetically modified maize and soybean in food

Abstract: The aim of this study was to analyze quantitatively the presence of genetically modified organism in food with different composition and degree of processing. Total DNA was extracted by Dellaporta's method and GMO analysis was performed using two consecutives PCR reactions with specie specific primers (IVR and LE), screening primers (35S) and transgen specific primers (CRY and EPSPS). The quantification within the sensitivity establish by the EU was possible only in some foods (ice-cream, flours, soybean isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It was demonstrated by Cazzola and Petruccelli (2006) that semi-quantitative analysis could be applied on the simple food samples contained maize and soybean. Studer et al (1998) reported that under certain circumstances, could be considered and used semi-quantitative method, but not routinely in GMO detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated by Cazzola and Petruccelli (2006) that semi-quantitative analysis could be applied on the simple food samples contained maize and soybean. Studer et al (1998) reported that under certain circumstances, could be considered and used semi-quantitative method, but not routinely in GMO detection.…”
Section: Resultsmentioning
confidence: 99%
“…The linear range obtained was 0.05% to 1% GMO as was described by Cazzola and Petruccelli (2006). Reaction condition for RT73, RF3 and T45 were adjusted to quantify with a treshold level of 0.05% (w/w).…”
Section: Pcrmentioning
confidence: 99%
“…Some major concerns about GM foods are addressed due to this phenomenon [4] . The presence of genetically modified organism in food with different composition and degree of processing was analyzed quantitatively [5] . Fully validated real-time PCR methods have been selected to detect the combination of five DNA sequences which was targeted by this screening method for the detection of genetically modified plant material in food and feed [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Underwood et al (1994) were the first to propose the determination of the number of genes by comparing samples with a standard curve, plotted based on DNA amplification of samples with previously determined gene dosages. In the last years, semiquantification works have been carried out in a similar way in a wide range of cases such as in the investigation of human diseases (diagnosis and determination of cytomegalovirus load in the leukocytes of bone marrow or kidney transplant patients (Marin et al, 2004) and determination of interferon-gamma mRNA levels in AIDS-free HIV-infected individuals (Barabás et al, 2001)), the identification of mixtures containing conventional and genetically modified maize seeds (Tozzini et al, 2000), or the determination of transgenic maize and soybean composition in processed foods (Cazzola and Petrucelli, 2006). However, its longest and most frequent use is in the analysis of gene expression, that is SQPCR, for instance, in the study carried out by Chelly et al (1990) concerning the expression analysis of the gene for muscular dystrophy, or in the distinction between queen and worker bees according to the production of mRNA for the enzyme methyltransferase (Baffi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although SQPCR does not permit an absolute quantification, the above-mentioned works demonstrated that it was possible to estimate the relative amount (Chelly et al, 1990;Baffi et al, 2004;Dutta et al, 2007;Tao et al, 2007) or the number of amplified molecules in each sample (Underwood et al, 1994;Tozzini et al, 2000;Marin et al, 2004;Cazzola and Petrucelli, 2006). The sensitivity of SQPCR is the result of a chain reaction, in which the products from one amplification cycle serve as substrates for the next, resulting in an exponential increase of the product.…”
Section: Introductionmentioning
confidence: 99%